Floricultural products : a study of major markets (ITC UNCTAD/GATT GenevaCH, 1987)
Market study of cut flowers, foliage and potted plants in Germany F R, France, UK, Netherlands, USA, Canada, and Switzerland. Gives overview of world trade, main non-European and tropical suppliers to countries studied and practical considerations on establishing export production; for each country gives comments and data on general market characteristics and opportunities, on specific market trends and prospects, and gives selected useful addresses.
IDS